Heavy metal pollution and ischemic stroke: multimechanistic pathogenesis and countermeasures - Liu, Junge; Wu, Lin (Frontiers in Public Health, 2025)
Heavy metal pollution is a significant environmental risk factor that profoundly impacts cerebrovascular health, particularly in the pathophysiology of ischemic stroke. This article outlines the relationship between metal exposure and stroke risk, highlighting regional differences potentially caused by contaminated food chains and industrial processes. We provide an in-depth discussion on the complex roles of lead (Pb), cadmium (Cd), arsenic (As), mercury (Hg), copper (Cu), and zinc (Zn) in the pathophysiology of stroke, with a particular focus on five key mechanisms: redox imbalance, neurotransmitter dysregulation, neuroinflammation, endothelial dysfunction, and coagulation disorders. Additionally, the review summarizes recent targeted therapeutic strategies for heavy metals, including antioxidants, metal chelators, inflammasome inhibitors, and epigenetic modifications, which show promise in neuroprotection. Research indicates that these strategies offer new perspectives for precision medicine in stroke treatment. We emphasize the importance of considering environmental factors in stroke prevention and advocate for pollution reduction as a means to improve public health. This review integrates molecular neuroscience and environmental toxicology, providing new insights and potential solutions to address the cerebrovascular diseases associated with heavy metals. These findings not only enhance our understanding of stroke’s pathophysiological mechanisms but also lay the foundation for future clinical treatment and prevention strategies.